(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In various physiological stages of the postnatal ontogeny of Karakol and Hisori sheep raised in the regions of Uzbekistan with different natural conditions, the compact substance and the degree of strength of the tubular bones in the distal part of the legs were studied. It was observed that the thickness of the compact substance of the metapodial bones is higher in animals with adequate conditions in the mountainous region; Due to the location of the bones in the leg skeleton and the level of weight force applied to them, the maximum force used to break the calcaneus was found to be higher than that of the palmar bone; the highest values of the strength limit of bones about compression are observed at 3 and 18 months of postnatal development, and at the following stages, this process practically stops, and even in 36-month-old animals, its significant decrease is noted.